Modeling and Parameter Calibration of Morchella Seed Based on Discrete Element Method - Min Li; Xiaowei He; Guansan Zhu; Jinxiu Liu; Kangcheng Gou; Xufeng Wang (Applied Sciences)
Studies on the discrete element method (DEM) parameters of Morchella seeds are limited due to their high moisture content and weak inter-particle adhesion. However, accurate DEM simulations are crucial for the design of agricultural machinery. Physical experiments were conducted to measure the fundamental properties of Morchella seeds, and a DEM model was established using the Hertz–Mindlin with JKR contact model. Subsequently, Plackett–Burman, steepest ascent, and Box–Behnken experiments were employed. They were used to analyze the significance of key contact parameters. A second-order polynomial regression model for the repose angle was developed, and significant contact parameters were optimized and calibrated. The results showed that the seed-to-seed rolling friction coefficient, seed-to-seed surface energy, and seed-to-steel rolling friction coefficient significantly impacted the repose angle. The simulation results using the optimized contact parameters closely matched the repose angle measured in physical experiments. The relative error was only 0.16%, validating the accuracy of the parameter calibration.